PENDIDIKAN DI ERA DIGITAL MEMBAWA INOVASI UNTUK KEMAJUAN SISWA - Rustiawan, Gede; I Ketut Suparya; Komang Trisna Mahartini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the impact of education in the digital era on students’ development. The rise of digital technology has introduced various innovations in the field of education, but it also raises questions about whether these advancements truly provide tangible benefits for students or merely create an illusion of progress. The main objective of this research is to explore how digital technology influences the quality of education, changes in teaching methods, and its effects on student achievement. The study employs a literature review method by analyzing various academic sources, including articles, journals, and publications related to the topic. The findings reveal that while digital technology can enrich students’ learning experiences and broaden their access to educational resources, there are also challenges such as digital inequality, dependence on technology, and the potential loss of social interaction in the learning process. Therefore, achieving sustainable educational progress requires the wise and balanced use of technology alongside teaching approaches that support students’ holistic development. Collaboration among educators, the government, and the community is essential to ensure that digital innovation truly brings meaningful and lasting benefits to the future of education.